Innovative Approach of Learning the Quality Management Course Contents Through Collaborative Learning in the Classroom - Hatte, Prafulla Ratnakar; Patil, Sagar Dnyandev; Malge, Abhijit Manikrao; Pande, Sandeep (Journal of Engineering Education Transformations, 2025)
Collaborative learning is an activity where students collaborate in groups with peers. This enhanced learning innovative approach is based on the collaborative learning activity conducted in the classroom for the third-year Mechanical students for the course Quality Management. The students were divided into small groups and for each group separate contents were assigned for learning. The learning resources were searched by the students on the net using mobile phones. All the students in the class were involved in learning. After 45 minutes, each group presented their learning, followed by question-answers. Formative assessment was associated with this learning activity. Collaborative learning helped the students not only learn the contents of the course but also enhance skills like group dynamics, Google searching, effective presentations, writing skills, and oral communication. Overall, the average feedback on the activity was observed to be 8.89 on a scale of 1 to 10.